The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ani12202865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Protein Supplementation at Mid-Gestation of Cows on Intake, Digestibility, and Feeding Behavior of the Offspring

Abstract: This study aimed to assess the effects of maternal protein supplementation and offspring sex (OS) on the intake parameters of the offspring. Forty-three Tabapuã cows were randomly allocated in the following treatments: protein supplementation (PS) during days 100–200 of gestation (RES, 5.5% total crude protein (CP), n = 2, or CON, 10% total CP, n = 19) and OS (females, n = 20; males, n = 23). The offspring were evaluated during the cow–calf (0–210 days), backgrounding (255–320 days), growing 1 (321–381 days), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Both repetitions had the same experimental procedures. Details of the experimental design were previously described by Nascimento et al [ 18 ] and Meneses [ 24 ]. Briefly, 52 multiparous Tabapuã beef cows ( Bos taurus indicus , yr 1: n = 25; yr 2: n = 27) were inseminated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both repetitions had the same experimental procedures. Details of the experimental design were previously described by Nascimento et al [ 18 ] and Meneses [ 24 ]. Briefly, 52 multiparous Tabapuã beef cows ( Bos taurus indicus , yr 1: n = 25; yr 2: n = 27) were inseminated.…”
Section: Methodsmentioning
confidence: 99%
“…Nitrogen-based supplementation improves low-quality pasture digestibility, leading to positive associative effects on the dry matter intake of ruminants [ 14 , 15 , 16 ]. This condition reflects greater nutrient availability for maternal gain, improving the pregnant component’s weight (as a fetus, amniotic fluid, placenta, and uterus) and the calf’s birth weight [ 17 , 18 ]. Moreover, the mid-gestation represents an opportunity to perform strategic protein supplementation for breeding herds.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, Hammer et al (2011) reported that lambs from ewes subjected to nutritional restriction had better immunoglobulin absorption efficiency during the first hours after birth, while Meyer et al (2010) demonstrated that intestines of fetuses of restricted dams presented increased proliferation and vascularization. Available evidence demonstrated greater nutrient digestibility in the feedlot phase for male offspring from dams fed low protein levels during mid-gestation (Nascimento et al, 2022) and that moderate protein restriction during mid and late gestation resulted in greater gut expression of genes involved with glucose and fatty acids metabolism (Cruz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%